Relationship between human development index and the sport results of Brazilian swimming athletes - Gomes-Sentone, R.; Lopez-Gil, J. F.; Caetano, C. I.; Cavichioll, F. R. (Journal of Human Sport & Exercise, 2019)
The identification of sports talents has been scientifically studied exploring epidemiological factors as predictors of success. Seeking to advance research of this nature, the present study aims to identify the relationship between the human development index (HDI) and the sports outcome of Brazilian swimming athletes. Method: the ranking of the Brazilian Water Sports Confederation between 2013-2017 was used for all age categories and swimming events from 1st to 100th place. The city where the athletes train was divided into categories according to the HDI being very high (1), high (2), medium (3), low (4) and very low (5), and the HDI in four indexes: general, income, longevity and education. Descriptive statistics were made for the number of cities and athletes according to the HDI. The assumption of normality was verified by the Kolmogorov-Smirnov test. To find correlations between variables, the Spearman Rho test for nonparametric variables was used to find the chance of having sports performance as a function of the HDI. 12271 athletes, 5230 women and 7041 men in 192 cities were identified. There was a positive correlation for overall HDI, income and education for men and women (p< .00); not so for longevity. Results: higher chances of having a sports athlete in swimming were found in cities with very high overall HDI (OR = 2.83; 95% CI = 1.95-4.11), demonstrating 6.2 times more likely to have swimming athletes in HDI income city. Conclusion: The overall HDI, income and education were relevant social indicators in identifying athletes with sports performance.